Obstetric medicine a problem-based approach - Nelson-Piercy, Catherine. (Springer London, 2007)
Medical problems in pregnancy are responsible for much maternal and fetal morbidity and mortality. This book is a collection of exam questions and case studies which illustrates both common and more unusual problems in obstetric medicine. Using a problem–based approach to both teach and test knowledge, it incorporates many different approaches to obstetric medicine, in Q & A format. The ‘extended matched questions’ section covers the breadth of theoretical knowledge. The ‘short answers/data interpretation’ section requires a systematic approach to a clinical problem. Most of the case reports are based on real cases and all are accompanied by a brief literature review to further broaden the learning experience. This book is a valuable learning and exam preparation guide which enables trainees and consultants to test themselves using the different methods, as well as read about medical problems in pregnancy they may not yet have encountered. Multiple choice questions -- Extended matching questions -- Short answer questions/data interpretation/clinical scenarios -- Essay questions -- Case studies.